Relationship between maternal knowledge and compliance with measles-rubella immunization - Maryati; Salmarini, Desilestia Dwi; Kusvitasari, Hairiana; Darsono, Putri Vidiasari (Ananda - Health & Education Foundation, 2025)
Background: Measles and Rubella are significant health threats to children, which can be prevented through immunization. Despite the availability of the Measles-Rubella (MR) vaccine, its coverage remains insufficient. Lack of maternal knowledge is a major factor contributing to non-compliance with the vaccination schedule. Objective: This study aims to assess the relationship between maternal knowledge and compliance with MR immunization for children under two years old. Method: A quantitative study with a descriptive analysis was conducted, involving 34 mothers with children aged 24-36 months at Long Kali Community Health Center. The total sampling method was used, and data were collected through a validated Guttman-scale questionnaire. Chi-square tests were employed to analyze the relationship between maternal knowledge and immunization compliance. Result: The study found that a significant proportion of mothers had poor knowledge (55.9%) about MR immunization. Furthermore, 70.6% of mothers were non-compliant with the MR immunization schedule. A significant association was identified between maternal knowledge and immunization compliance (p < 0.05). Conclusion: Maternal knowledge significantly influences compliance with the MR immunization schedule. Efforts to increase awareness and understanding of MR immunization are crucial to improve vaccine uptake and protect children from preventable diseases.